Industrial Noise Pollution and its Impacts on Workers in the Textile Based Cottage Industries: An Empirical Study - Aitbar Ali Abbasi; Hussain BuxMarri; Murlidhar Nebhwani (Mehran University Research Journal of Engineering and Technology, 2011)
This study includes the research work which was carried out to investigate the range of difficulties faced by the workers and its effects on them while working in textile based cottage industries along with their causes. This research provides necessary tip-offs to solve those problems in a systematic way. Therefore, it was considered to know the number of machines (looms) operated by one worker, number of machines in one unit and number of operators in one unit. The minimum and maximum noise levels were recorded by using digital sound level meter to compute average noise level/ unit. To identify the health problems like respiratory, hearing/listening, irritation, heart/BP, annoyance and headache faced by the workers, the survey was conducted. In present research work the minimum noise recorded was 101.6dB (A) and maximum as 109.8dB (A), which was compared with OSHA and WHO (World Health Organization) standards. Result of this study shows that due to high intensity of noise generated by looms and dusts at work places, workers were facing the mental and physical problems.